The Role of Small Business in the Competitive Development of Different Countries in Conditions of Instability ("Journal "U". Economy. Management. Finance.", 2017)
An analysis of influence of small business on the economy competitiveness of different countries is presented in the article. A comparison of criteria for the classification of enterprises as well as measures and programmes to support small business in Russia and other countries is performed. The analytical data reflecting the state of small business in Russia is presented.
Keywords: small enterprise; entrepreneurship; small business; startup; government regulation of business; competitiveness; business support programs; small business support